Using CAMEL’S Rating System in Achieving Financial Soundness in Banks (مجلة المنصور, 2023)
The research aims to determine the CAMELS rating system role as one of uniform Banks evaluation systems with its sixth elements in verifying financial soundness in banks which become one of the significant subject which has an academic and bankers interest all the same through the dynamics and complexity Financial and Banking Environment, and what this environment faces from crises influence on banking and financial sector in deferent countries.As ample was chosen from private banks in Iraq to verify the research aim, the research concluded that there is a relation between Camels rating system results and financial Soundness in banks measured by Finical performance indicators, and the research recommended the necessity which the central bank has to determine the mechanism for supervising the bank which have a bad evaluation to preserve the financial soundness of the financial system.